Towards E-CASE Tools for Software Engineering - Arman, Nabil (International Journal of Advanced Corporate Learning (iJAC), 2013)
CASE tools are having an important role in all phases of software systems development and engineering. This is evident in the huge benefits obtained from using these tools including their cost-effectiveness, rapid software application development, and improving the possibility of software reuse to name just a few. In this paper, the idea of moving towards E-CASE tools, rather than traditional CASE tools, is advocated since these E-CASE tools have all the benefits and advantages of traditional CASE tools and add to that all the benefits of web technology. This is presented by focusing on the role of E-CASE tools in facilitating the trend of telecommuting and virtual workplaces among software engineering and information technology professionals. In addition, E-CASE tools integrates smoothly with the trend of E-learning in conducting software engineering courses. Finally, two surveys were conducted for a group of software engineering professional and students of software engineering courses. The surveys show that E-CASE tools are of great value to both communities of students and professionals of software engineering.